USING THE EXPERIENCE OF COUNTRIES OF THE WORLD IN THE SOCIAL DEVELOPMENT OF OUR COUNTRY (BY THE EXAMPLE OF SINGAPORE) (Scientific journal of the Fergana State University, 2024)
Today, every country strives to achieve a high level of development and take a place among developed countries. Drawing on the experience of countries with high development indicators will also bring great results. In order to achieve high results in social development, a number of reforms and updates are being carried out in our country. In this regard, in addition to reforming all areas, the experience of developed countries is effectively used. This article presents opinions and practical proposals for the further development of our country, finding solutions to existing problems based on the experiences of developed countries around the world, in particular Singapore. The research work used methods of historicity, coherence, consistency, observation, comparison, and analogy. A number of proposals have been put forward to solve existing problems. Based on the experience of Singapore, specific conclusions were given for the further development of our country.